A low-carbohydrate diet is more effective in reducing body weight than healthy eating in both diabetic and non-diabetic subjects. - Dyson, P; Beatty, S; Matthews, DR (2007)
BACKGROUND: Low-carbohydrate diets are effective for weight reduction in people without diabetes, but there is limited evidence for people with Type 2 diabetes. Aims To assess the impact of a low-carbohydrate diet on body weight, glycated haemoglobin (HbA(1c)), ketone and lipid levels in diabetic and non-diabetic subjects. METHODS: Thirteen Type 2 diabetic subjects (on diet or metformin) and 13 non-diabetic subjects were randomly allocated to either a low-carbohydrate diet (< or = 40 g carbohydrate/day) or a healthy-eating diet following Diabetes UK nutritional recommendations and were seen monthly for 3 months. Subjects (25% male) were (mean +/- sd) age 52 +/- 9 years, weight 96.3 +/- 16.6 kg, body mass index 35.1 kg/m(2), HbA(1c) 6.6 +/- 1.1%, total cholesterol 5.1 +/- 1.1 mmol/l, high-density lipoprotein cholesterol 1.3 +/- 0.4 mmol/l, low-density lipoprotein cholesterol 3.1 +/- 0.9 mmol/l, triglycerides (geometric mean) 1.55 (1.10, 2.35) mmol/l and ketones range 0.0-0.2 mmol/l. RESULTS: Analysis was by intention to treat with last observation carried forward. Twenty-two of the participants (85%) completed the study. Weight loss was greater (6.9 vs. 2.1 kg, P = 0.003) in the low-carbohydrate group, with no difference in changes in HbA(1c), ketone or lipid levels. CONCLUSIONS: The diet was equally effective in those with and without diabetes.